Biodegradable fixation pins for interphalangeal joint arthrodesis in lesser toe deformity and fracture correction – A retrospective follow-up of 31 toes - Helka Koivu, MD, PhD; Ilona Koski, MD (Foot & Ankle Surgery: Techniques, Reports & Cases, 2023)
Lesser toe deformities are commonly surgically treated with interphalangeal joint arthrodesis using different internal fixation implants with good results. There are few studies reporting the results of the use of bioabsorbable implants. The aim of this study was to investigate the clinical and radiological outcomes of lesser toe interphalangeal joint arthrodesis using a novel biodegradable pin as fixation method. Consecutive patients operated by proximal (PIPJ) or distal interphalangeal joint (DIPJ) arthrodesis using the Inion FreedomPin™ (Inion Oy, Tampere, Finland) with a minimum of 12 months of follow-up were retrospectively evaluated both clinically and radiologically. 21 patients (age 34–78, median 60 years) with 24 feet and 31 toes were available with a median follow-up of 26 (range 12–40) months. Clinical alignment was good in all but one toe. There were no complications and patient satisfaction was high. The radiological alignment was corrected in 25, partially corrected in five, and not corrected in one toe. A complete radiological bony fusion was detected in 25 (81%), partial in one (3%), and no fusion in five (16%) toes. In conclusion, the Inion FreedomPin™ bioabsorbable pin had clinically and radiologically favourable outcome for lesser toe interphalangeal joint arthrodesis.